MANAGEMENT OF SECURITY FOR BANK LOANS ON THE BASIS OF RISK MANAGEMENT - Kovalenko , V.V. (The actual problems of regional economy development, 2016)
The article aims to study methods and tools for risk management to ensure bank loans. Proved that the effectiveness of risk management to ensure bank loans depends on consistency, adequacy methods of evaluation, quality monitoring and timely response system of the banks and the regulator. The article is to develop recommendations to improve the effectiveness of risk management providing bank loans considering the risks inherent in the process support mortgage portfolio of banks in the face of considerable uncertainty functioning banks. It is proved that the risk provision of bank loans in the loan management should be considered through risk characteristics that form the aggregate credit risk. Substantiated that risk management software meets the classic risk management, which identifies four main stages: identification; risk assessment software; control risk; minimizing risk. JEL: G 28